Percepcões de professores de biologia sobre a transversalidade do tema meio ambiente no ensino médio - Andrade, Elzimeire Abreu Araújo (2019)
A polemic persists about the ways to insert the theme “environment” in the curriculum of the Brazilian basic school: to create a discipline or to the mainstream it? With the polemic also persist the different conceptions and perceptions of the teachers about the concepts of environment and the field of action of environmental Education. After that, in this study we sought to investigate the perceptions of a group of Biology teachers in the educational network of the State of Espírito Santo on: (1) the concepts of environment, (2) the field of environmental education and (3) the ways in which it is addressed in the curriculum. Using a mixed research approach, the data were produced through the application of a semi-structured questionnaire with 28 teachers from 23 schools located in 14 cities. The results obtained evidenced that 42% of the participants already had some access to courses, projects or specific environmental education events. When indicating themes that should be addressed in environmental education activities, teachers indicated economics, partisan politics, prejudice, poverty, social inequality and infant mortality, with a frequency below 70%, while sustainable development, pollution, ecosystem conservation, species extinction and Global warming had frequencies ranging between 90% to 100%. Therefore, it can be inferred that in the perception of the teachers are different macro trends, but with prevalence of the naturalistic concept of environment. Within the perception about the most urgent environmental issues to be addressed in secondary education, according to the geographical scales (community, municipality and state), it was registered a total of 91 evocations divided into 24 themes that were grouped according to Santos (2007) guidelines for which the following frequencies were obtained: (1) Pedagogy of the nonhuman nature: 17.58%; (2) Pedagogy of human nature: 48.35% and (3) Integrative pedagogy: 34.06%. A total of 46.42% of the teachers defended the creation of an Environmental Education discipline, whose justifications were: the low hours of their subjects, the relevance of the subject that is little discussed in other disciplines, the complexity of the subject and the teacher‟s unpreparedness. However, 59.25% of teachers state that all disciplines are appropriate to address the environmental theme, although they also claim that Biology and Geography are more proper than others. The naturalistic feature in perception was corroborated when 39.28% stated that Biology is important for Environmental Education because it favors the awareness and protection of biodiversity. Only 10.71% declared their importance due to their potential for critical formation. Among the difficulties to approach environmental education, stood out: the need to gather knowledge from different areas, the legal aspects that involve the theme and lack of infrastructure of the schools. The predominant didactic strategies were the lectures, indicated by 36.36%, followed by reading and interpretation of texts with 22.72%. From the results, the limitations and possibilities for the accomplishment of the transversality of the environmental theme in the discipline of Biology were discussed. In addition, the results served as input for the development of a guide that could contribute with the teacher in the task of identifying, in the contents of Biology, the opportunities to approach socio-environmental themes, therefore fulfilling the task of the theme‟s transversality.